2008
DOI: 10.3171/spi.2008.9.0861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with postoperative infection following sacral tumor resection

Abstract: Object Resection of sacral tumors has been shown to improve survival, since the oncological prognosis is commonly correlated with the extent of local tumor control. However, extensive soft-tissue resection in close proximity to the rectum may predispose patients to wound complications and infection. To identify potential risk factors, a review of clinical outcomes for sacral tumor resections over the past 5 years at a single institution was completed, paying special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 26 publications
0
41
2
3
Order By: Relevance
“…Sacral procedures have had historically higher rates of infection than other spinal procedures [5][6][7][8][9][10]. Primary sacral tumors are rare, and experience with postoperative wound complications of these tumors is, therefore, limited to observations on less than 80 patients [2,[11][12][13][14][15][16][17][18]. The postoperative infection rates were 8.3-39.1 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sacral procedures have had historically higher rates of infection than other spinal procedures [5][6][7][8][9][10]. Primary sacral tumors are rare, and experience with postoperative wound complications of these tumors is, therefore, limited to observations on less than 80 patients [2,[11][12][13][14][15][16][17][18]. The postoperative infection rates were 8.3-39.1 %.…”
Section: Discussionmentioning
confidence: 99%
“…One of the aims of our study was to define the significant factors that contribute to an increased incidence of wound complications. As in most studies, we selected SSI as the dependent variable [10,13]. Wound dehiscence, which is also a major wound complication, also occurred frequently in this series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Five additional potentially relevant studies were identified from reference lists. Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…[34][35][36][46][47][48]50,52,65,67,68,78,80,81,[86][87][88]95,100 It is especially important to understand the incidence and predictive factors for adverse events in spinal oncology patients, as a single complication may be associated with morbidity, mortality, and costs. 1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, 48,52,65,74,86,93,98 and prior studies have identified anatomical location, tumor size, tumor histology, extent of resection, surgical approaches, age, functional status, comorbidities, preoperative medication (steroid use, morphine), longer operative time, insurance status, early postoperative complications, and adjuvant chemotherapy and radiotherapy as factors associated with postoperative morbidity and mortality. 1,[18][19][20][21][22][23]…”
mentioning
confidence: 99%